Trusts and modern wealth management - NOLAN, Richard C. (Institutional Knowledge at Singapore Management University, 2018)
Trust law has grown and developed over recent years through the continued ingenuity of practitioners and the provision of innovative new trust laws by offshore jurisdictions. The wealth managed through the medium of trust law has also changed in recent years, as increasingly it has come from the newly rich of Asia. This brings distinctive issues to the fore: the role of settlors, family members and trusted advisors in trust administration; the position of trustees in relation to instructions coming from such persons; and an increased desire for confidentiality in trust administration and the settlement of trust disputes. This collection focuses on trusts which are deliberately created to manage wealth and the concomitant issues such trusts raise in other areas of law. Essays from leading members of the judiciary, practitioners and academics explore these developments and their implications for the users of trust law and for society in general.